Recent understanding of the etiopathogenesis of psoriasis - Aparajita Ghosh; Saumya Panda (Wolters Kluwer Medknow Publications, 2017)
Psoriasis is a common inflammatory disorder of the skin. Although a lot is known regarding its pathogenesis, much remains to be elucidated and understood. Psoriasis is a disease of multifactorial origin where certain environmental factors acting on individuals with specific genetic predisposition leads to an immune dysregulation. Till now no single genetic or environmental entity has been found to be consistently associated with all cases of psoriasis. Hence, psoriasis has been considered by some to be a heterogeneous group of disorders where several disparate pathological processes result in a similar outcome. There is a huge array of potential genes now implicated and an equally large array of molecules (chemokines, cytokines, inflammatory mediators, signal transduction molecules, and transcription factors) found to be involved. Although new therapeutic options have opened up as a result, our inability to solve the puzzle and thoroughly understand the disease prevents their optimal utilization.